2021
DOI: 10.3390/coatings11121454
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Polyurethane Binder Curing Reaction and Evaluation of Polyurethane Mixture Properties

Abstract: This study focuses on analyzing the curing reaction mechanism of polyurethane (PU) binders and comprehensively evaluating the PU mixture’s properties. The former was investigated by conducting a Fourier transform infrared spectroscopy (FTIR) test on PU binders with different curing times. The volume change characteristics, construction operation time, and strength formation law were clarified through the splitting tensile test of PU mixtures under different environmental conditions. The optimal PU mixture stac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The reason for this is that asphalt is a temperature-sensitive binder. Increases in the temperature lead to a transition of asphalt from an elastic state to a viscous state, which affects its mechanical properties [ 16 ]. The strength of the PU mixture is formed by the curing reaction of the PU binder, which is irreversible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for this is that asphalt is a temperature-sensitive binder. Increases in the temperature lead to a transition of asphalt from an elastic state to a viscous state, which affects its mechanical properties [ 16 ]. The strength of the PU mixture is formed by the curing reaction of the PU binder, which is irreversible.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, according to the ultimate bearing capacity and stress level, the control stresses of the five mixtures are calculated. Previous studies have shown that the fatigue life of PU mixtures is long [ 16 , 17 ], so the stress levels of asphalt mixtures are 0.3, 0.4, and 0.5, and the stress levels of PU mixtures are 0.5, 0.6, and 0.7.…”
Section: Test Scheme and Calculation Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…At present, PU mixture is mainly studied in three aspects: functional pavement, pavement structural layer, and bridge deck pavement. The composition design, curing reaction mechanism, performance evaluation, and construction technology of PUM are being studied by an increasing number of researchers worldwide [16][17][18].…”
Section: Introductionmentioning
confidence: 99%